KEY MACROECONOMIC DETERMINANTS OF GOVERNMENT DEBT – THE CASE OF NORTH MACEDONIA - Filip Taskovski (Economic Review)
Government debt, as a prime macroeconomic determinant, has a significant impact on the design of fiscal and monetary policy in a country. That is to say, that, with the emergence of the Corona crisis and the energy crisis which caused: 1) interruption of global supply chains, 2) increase in food and energy prices and 3) interruption of the balance of supply and demand, a large number of countries including North Macedonia began to create targeted anti-crisis measures that caused the growth of the budget deficit, and as a result of this, the government’s debt increased. What is characteristic about North Macedonia is that the increase of the government’s debt caused the growth of the public debt, whereby it exceeded 60% of the GDP, which also means violation of one of the Maastricht criteria for convergence. The focus of this paper is the determination of the effect of key macroeconomic determinants on the government’s debt of North Macedonia. This research paper is based on secondary data from relevant sources such as the Ministry of Finance and the National Bank of the Republic of North Macedonia, the State Statistics Office and the IMF.  The multiple linear regression model was applied in the empirical part of the research, in which five variables are incorporated. In this model, the government’s debt, as a percentage of GDP is the dependent variable, and the annual economic growth, the average annual inflation rate, the budget deficit and the annual amount of FDI are independent variables.             Based on the results of the research, it can be concluded that the world crisis has a strong impact on the public finances of North Macedonia, and the growth of the budget deficit largely causes the growth of the country's debt by the government.